Innovative approaches for quality planting material production in tropical tuber crops - Muthuraj, R; Jaganathan, D (Indian Horticulture, 2025)
Tropical tuber crops such as cassava, sweet potato, yams, taro, and elephant foot yam are vital food security crops, especially in marginal and adverse environments. However, their vegetative mode of propagation and low multiplication rates hinder the rapid dissemination of improved varieties. This paper highlights innovative approaches for quality planting material productionto overcome these challenges. Techniques such as the minisett method and tissue culture-based meristem propagation have significantly enhanced multiplication ratios and ensured disease-free planting material. Decentralized models like SeedVillages and Decentralized Seed Multipliers (DSM) have empowered farmers with access to timely, high-quality seed. Additional innovations such as poly tunnel nurseries, vertical farming, and contract farming are also being integrated to scale up production and expand cultivation to non-traditional areas. These farmer-centric strategies have shown promising results in improving productivity,profitability, and self-reliance, contributing to the larger vision of ensuring food and nutritional security under the ‘Viksit Bharat’ initiative.